Development of Augmented Reality to Solve Geometry HOTS Problems for Class V SDN 1 Doplang Students - Ahmad Ridlo Setiawan; Nursiwi Nugraheni (STKIP Singkawang, 2025)
The results of the initial interview were explained by the class teacher that grade V students of SDN 1 Doplang still had difficulty doing high-level questions, especially on geometry material. Then the observations also prove that in general, teachers still use models and learning media only in the form of pictures and videos. The purpose of this study is to develop augmented reality learning media based on geobar applications so that it can facilitate students in the process of understanding geometry material. The type of research used is research and development (RnD) with the Borg and Gall model which is modified into 9 stages. Data collection techniques through observation, interviews, questionnaires, and documentation. Results of the product assessment are in the form of validation of learning media carried out by material, media, and language experts with percentages of 91.6%, 90.6%, and 93.1% with a classification of